FORMATION OF PROFESSIONAL COMPETENCE OF STUDENTS BY MEANS OF PRACTICALLY-ORIENTED INTERACTIVE LEARNING (Journal of Information Technologies in Education (ITE), 2013)
In the paper practical-oriented interactive teaching methods of economists, such as mind mapping, case method and information technologies of teaching are analyzed.
Keywords: mind mapping; case method; information technologies of teaching; electronic diary